Self-assembling peptide scaffolds in the clinic - Fabrizio Gelain (Nature Portfolio, 2021)
Abstract Well-defined scaffold hydrogels made of self-assembling peptides have found their way into clinical products. By examining the properties and applications of two self-assembling peptides—EAK16 and RADA16—we highlight the potential for translating designer biological scaffolds into commercial products.